Analysis of the bosonic pair creation in a static potential well. (5th August 2021) - Jiang, M; Lin, N S; Su, D D; Li, Y J
Abstract: We study the pair creation process of bosonic systems in a time-independent potential well by numerically solving the Klein–Gordon equation. In order to study the effect of multiple bound states on the creation process, broad widths of the potential well are chosen. The energy eigenvalues are calculated by diagnosing the non-Hermitian Hamiltonian with applied fields, and the exponential growing factor of the number of created pairs is in accordance with twice of the maximum imaginary part among all the bound states. By investigating the interaction between the bound states and the negative energy continua in spectrum, the competition effect of multiple bound states in a bosonic pair creation process is discussed.